PROSPECTS OF INDONESIAN AGRARIAN LAW SYSTEM REFORM TO PROVIDE THE WELFARES - Lumbanraja, Anggita Doramia (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2023)
Agrarian law in Indonesia has not been able to provide prosperity to society. This can be seen from the injustices that arise from a number of regulations in the field of agrarian law, including the Job Creation Law. This article aims to examine whether Agrarian law in Indonesia reflects Pancasila and is based on the mandate of the constitution, and whether there is a need for reform. This research is doctrinal research using a literature study. This study finds that agrarian law policies in Indonesia are still not in favor of people who have a weak economic position. The development of globalization and the pressures of investment make government policies still pro favor those with a strong economic position. Therefore, it is very necessary to have a bill to improve the UUPA to realize a just national agrarian politics to realize the wider community's welfare. Consistency towards recognizing ulayat rights and customary law also needs to be enforced in all government legal policies. This needs to be emphasized in Indonesian legal politics.